Regulating prenuptial agreements in Malaysia: special reference to the position in United Kingdom and Australia / Nur Syazwani Sham Shul Baharin ... [et al.] - Sham Shul Baharin, Nur Syazwani; Ahmad, Nor Farhani; Burhan, Nur Farah Hanim; Zainalkefli, Zur Azureen (Faculty of Law, 2013)
Prenuptial agreement is a contract entered into before marriage. It sets out the terms on property or alimony division in the event divorce takes place is given legal recognition in countries such as Australia and United Kingdom. Malaysia however does not encourage prenuptial agreement because of the socio-culture that values the sanctity of marriage and the adequacy of the laws such as Law Reform (Marriage and Divorce) Act 1976 (LRA) that eloquently governs property division and alimony in the event of divorce. Hence, this project sets forth a. research on: i. The role and significance of a prenuptial agreement; and ii. Whether prenuptial agreement needs to be regulated in Malaysia in the event that it gains recognition over and above the provisions as provided in the LRA. The research findings upon comparative analysis of the laws between Malaysia, UK and Australia as well as interviews conducted, found that: i. There is no imminent need to regulate on prenuptial agreement because of the socio-culture and custom of the Asian society ii. The provision in the LRA gives a wide discretion to the judges to decide on property division and alimony. Nonetheless, in the event when prenuptial agreement gains recognition, it must be governed by proper provision.